Acoustical Evaluation and Comparative Study of Maple Leaves and Coir and Polyester Fibers. Issue 15 (23rd November 2022) - Yang, Tao; Hu, Lizhu; Xiong, Xiaoman; Venkataraman, Mohanapriya; Petrů, Michal; Novák, Jan; Militký, Jiří
ABSTRACT: In the last few years, concerns about the adverse effects of petroleum-based materials on the environment and public health have gradually increased. It is worthy and meaningful to find natural materials to substitute the conventional synthetic sound absorbers. The sound absorption properties of Norway maple leaves were investigated in this paper. The leaves laminated in 5 to 50 layers were measured in the low- to mid-frequency and mid- to high-frequency ranges in the impedance tubes. Later, the sound absorption performance of laminated leaves was compared with polyester, kapok, coir, and broom fibers. The results show that the 15 layers of leaves exhibit good sound absorption properties in the two frequency ranges. Moreover, the 15 layers leaves have comparable sound absorption performance to polyester and coir fibers. The results indicate that the maple leaves are the potential alternative material to synthetic material in a low-frequency range with a thin structure.